Factors related to social disconnectedness among older unpaid caregivers - Moka Yoo-Jeong; Jonathan Singer; Caroline D. Bergeron; Jodi L. Southerland; Hye Won Chai; Andrew C. Pickett; Yuanjin Zhou; Christian E. Vazquez; Juanita-Dawne Bacsu; Katherine Kwong; Wonkyung Jung; Tiffany R. Washington; et al. (Frontiers in Public Health)
BackgroundOlder unpaid caregivers often face social isolation and loneliness, yet risk factors for social disconnection remain largely unexplored. As the demand for unpaid caregiving rises with an aging population, there is a need for targeted interventions to reduce social disconnectedness in this vulnerable group. This study aimed to identify determinants of social disconnectedness.MethodsData came from a sample of 701 unpaid caregivers aged 60 + who completed an internet-based survey assessing sociodemographics, health status, financial strain, social environment, and social disconnectedness. Four sequential regression models were used to identify the unique contribution of these factors related to social disconnectedness.ResultsThe first model (F = 3.94, p < 0.001, aR2 = 0.030) showed that older age (β = −0.15, p < 0.001), self-identifying as being Black (β = −0.10, p = 0.008), and higher education (β = −0.11, p = 0.041) were associated with lower social disconnectedness. Adding health factors in the second model (F = 15.33, p < 0.001, aR2 = 0.170) revealed that, in addition to age and education, chronic conditions (β = 0.12, p = 0.001) and possible depression (β = 0.35, p < 0.001) were associated with social disconnectedness. Including financial strain in the third model (F = 15.52, p < 0.001, aR2 = 0.212) showed that household income (β = −0.10, p = 0.012) and financial stress (β = 0.18, p < 0.001) were additionally associated with social disconnectedness. The final model (F = 23.42, p < 0.001, aR2 = 0.366) that included social environmental factors showed that age (β = −0.07, p = 0.033), possible depression (β = 0.22, p < 0.001), financial stress (β = 0.16, p < 0.001), and levels of community belonging (β = −0.20–0.58, p < 0.001) were significantly related to the risk of disconnectedness.ConclusionFindings highlight possible intervention targets that have the potential to reduce social disconnectedness among older unpaid caregivers. Particularly, addressing depressive symptoms, reducing financial stress, and enhancing community belonging are essential components to mitigate social disconnectedness risk in this population.